Comparative Study: Internal Marketing Value of Shallot Hydroponic Performance Using NFT vs. DFT Across Two Growth Periods - Sundari, Ristina Siti; Pauzy, Depy Muhamad; Firmansyah, Hary; Arif, Arif; Purba, Jhon Hardy (Agro Bali : Agricultural Journal, 2025)
Urban farming has emerged as a strategic response to the challenges of land scarcity and food security in metropolitan areas. This study investigates the financial performance and internal marketing value of shallot (Allium cepa var. aggregatum) agribusiness cultivated hydroponically using Nutrient Film Technique (NFT) and Deep Flow Technique (DFT) systems across two planting cycles. Conducted as a case study at P4S Galih Jaya, the research employed a quantitative descriptive approach, combining direct observation, financial documentation review, and structured stakeholder interviews. Key metrics, production output, net income, Benefit-Cost (B/C) ratio, and Break-Even Point (BEP), were calculated using standard agribusiness financial formulas. Internal marketing indicators, including employee understanding, decision alignment, and motivation, were assessed through pre- and post-cycle surveys and integrated into participatory training sessions. Results indicated that the DFT system in cycle 2 yielded the highest net income (IDR 2,036,725) and B/C ratio (3.6), while the NFT system in cycle 1 incurred a financial loss (IDR -10,155) with a B/C ratio of 0.9. These findings were embedded into internal communication tools and stakeholder training sessions to foster data-driven decision-making. Internal marketing indicators showed marked improvement between periods, demonstrating the strategic value of integrating financial literacy into agribusiness operations. The study concludes that the selection of a hydroponic system not only affects profitability but also internal stakeholder engagement. The comparative study framework offers a replicable model for urban farmers seeking to align technical performance with internal adoption and strategic planning. Further research is recommended across successive planting periods to assess long-term viability and deepen internal marketing impact.